2016
DOI: 10.1155/2016/8612143
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for In-Hospital Complications of Fall-Related Fractures among Older Chinese: A Retrospective Study

Abstract: Purpose. The aim of this study was to investigate the risk factors and the efficacy of the preventive measurements for the in-hospital complications of fall-related fractures. Methods. The data on older Chinese patients with fall-related fractures were collected, including information on the patients, diseases, and preventive measurements. The potential risk factors for the in-hospital complications included health status on admission, comorbidity, fractures, preventive measures of the complications, and drugs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
14
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 32 publications
6
14
0
2
Order By: Relevance
“…There have been many geriatric and orthopedic studies showing that elderly persons are at risk of fractures due to falls. 12,29 This finding corresponds to that seen with maxillofacial fractures in the present study. 9,12 Falls in elderly persons have been reported to be associated with several chronic diseases, some acute diseases, any pain of the body, and medication use, such as cardiovascular or psychotropic drugs.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…There have been many geriatric and orthopedic studies showing that elderly persons are at risk of fractures due to falls. 12,29 This finding corresponds to that seen with maxillofacial fractures in the present study. 9,12 Falls in elderly persons have been reported to be associated with several chronic diseases, some acute diseases, any pain of the body, and medication use, such as cardiovascular or psychotropic drugs.…”
Section: Discussionsupporting
confidence: 91%
“…There have been many geriatric and orthopedic studies showing that elderly persons are at risk of fractures due to falls . This finding corresponds to that seen with maxillofacial fractures in the present study .…”
Section: Discussionsupporting
confidence: 91%
“…Thus, adequate staffing of NAs is as important as RN staffing to prevent patient falls. Although ADL dependency was a risk factor for falls (Lawlor, Patel, & Ebrahim, ; Pi et al, ; Rubenstein, ; Vassallo et al, ), nursing needs was not a factor affecting falls in this study. Previous studies have suggested that a patient’s medical condition was related to falls (Lawlor et al, ; Severo et al, ).…”
Section: Discussionmentioning
confidence: 52%
“…Several studies have reported that the higher the percentage of the elderly, the higher the incidence of falls (Hitcho et al, ; Rubenstein, Powers, & MacLean, ). Fall‐related injuries, like fractures, are a severe health problem themselves; however, they might be responsible for other severe health complications, such as infections or pressure ulcers (Pi et al, ; Sibley, Voth, Munce, Straus, & Jaglal, ). Thus, a serious injury from a fall is a serious threat to patient safety and adds a burden to patients, as well as hospitals.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it is worth noting that environmental aspects and human resources are identified as risk factors for fall 8 - 9 .…”
Section: Introductionmentioning
confidence: 99%